Research Progress on the Integrated Traditional Chinese and Western Medicine Therapy for Cancer-Related Anemia - Wen, Yaoqi; Zhao, Yanli; Li, Liangliang; Wang, Yupei (Journal of Contemporary Medical Practice, 2025)
Cancer-related anemia (CRA) is a common complication in patients with malignant tumors, which not only affects their quality of life but may also reduce the efficacy and tolerance of radiotherapy and chemotherapy. In recent years, integrated Traditional Chinese and Western medicine (TCM-WM) has demonstrated unique advantages in treating CRA. Modern medicine primarily employs therapies such as erythropoietin, iron supplementation, and blood transfusion, which have limitations and potential risks. Traditional Chinese Medicine (TCM), through treatment approaches like fortifying the spleen and nourishing the kidney, replenishing qi and blood, and activating blood circulation to remove stasis, improves the hematopoietic microenvironment and regulates the body’s immune function, showing increasing promise in recent years. By combining the strengths of both systems, integrated TCM-WM exhibits synergistic effects in elevating hemoglobin levels, improving clinical symptoms, reducing side effects of Western medical treatments, and enhancing the quality of life. Current research confirms its safety and efficacy; however, more high-quality, large-sample clinical studies are needed in the future to further explore its mechanisms of action and optimize diagnosis and treatment protocols.